SHIFT UPLOAD-UPLOAD JAVA LANGUAGE IN YOUTH GENERATIONS IN JAVANIC SOCIETY (Case Study in Tiudan Village Community): - Nagari, Kinawang (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2024)
Unggah-ungguh in Javanese society is a science that regulates the way a person behaves in accordance with Javanese culture. Unggah-ungguh Jawa is defined as a person's manners or manners, which is synonymous with the value of respect. Tiudan Village is one of the villages where the majority of the population is Javanese. The progress of this modern era has made rural communities experience a shift in their uploads towards older people. The purpose of this study was to determine the shift in uploading Javanese language in the younger generation in Javanese society. This study uses a qualitative approach with library research data collection techniques, literature review and direct observation. The results showed that the shift in uploading Javanese language to the younger generation in the Tiudan Village community was due to a lack of socialization to the younger generation, then the unggah-ungguh shift was caused by smartphones which made the younger generation in Tiudan Village lose respect and courtesy. The solution used in re-applying the value of unggah-ungguh the Javanese language is by way of socialization to the community which can be done through teaching in the family environment and in the educational environment. Keywords: Unggah-Ungguh, Young Generation, Javanese Society.